Natural history of dental caries: Baseline characteristics of the VicGen birth cohort study. Issue 3 (2nd January 2020) - Chattopadhyay, Amit; Christian, Bradley; Masood, Mohd.; Calache, Hanny; Carpenter, Lauren; Gibbs, Lisa; Gussy, Mark
Abstract: Background: Early‐life dental caries is a major global health problem. Children's first dental visit is recommended at 2 years age. The VicGeneration (VicGen) oral health birth cohort study aims to understand the multifactorial nature of early childhood caries. This report describes the baseline characteristics of children in the VicGen study. Methods: We merged data between the first (at birth) and fourth waves (18 month age) to assess dental caries among children (primary outcome) and other oral diseases (secondary outcomes) employing t tests, chi‐square tests, Fisher's exact tests, and Cochran‐Mantel‐Haenszel tests using IBM‐SPSS(v25). Results: Most children lived in metros with two‐parent families. Most guardians were women graduated from high school. Twenty‐seven of 389 (6.94%) 18‐month‐old children experienced dental caries. More children living in rural areas (vs. urban) experienced caries. Females were more likely to experience caries (OR: 2.16). Several children had other oral health problems. In early life, children's oral examination was conducted by midwives, breastfeeding/lactation consultants, hospital nurses, speech pathologists, and breastfeeding clinic staff. Conclusion: VicGen baseline characteristics show that almost 7% of the 18‐month‐old children experienced caries. There is a need to advance children's recommended first dental visit date and to train early‐life healthcare professionals about oral diseases.